2016
DOI: 10.1016/j.ajog.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Do serial measurements of cervical length improve the prediction of preterm birth in asymptomatic women with twin gestations?

Abstract: Objective To determine whether serial measurements of cervical length can improve the prediction of preterm birth in asymptomatic women with twin gestations compared with a single measurement of cervical length at mid-gestation. Materials and Methods This was a retrospective cohort study of women with twin pregnancies followed in a tertiary medical center between 2012 and 2014. All participants underwent routine measurement of cervical length at mid-gestation and every 2–3 weeks thereafter until 28–32 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 127 publications
(50 reference statements)
1
29
0
2
Order By: Relevance
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 15 Twin pregnancies are at higher risks of preterm delivery and a recent retrospective cohort study of 441 women with twin pregnancies has found that integration of serial measurements of CL using a stepwise algorithm in asymptomatic women with twin gestations can improve the detection of women at risk of preterm birth. 46 Women with VP in a MC twin pregnancy also require a regular follow-up to assess the risks of TTTS and thus determining the twin chorionicity is pivotal in the management of these high-risk pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 15 Twin pregnancies are at higher risks of preterm delivery and a recent retrospective cohort study of 441 women with twin pregnancies has found that integration of serial measurements of CL using a stepwise algorithm in asymptomatic women with twin gestations can improve the detection of women at risk of preterm birth. 46 Women with VP in a MC twin pregnancy also require a regular follow-up to assess the risks of TTTS and thus determining the twin chorionicity is pivotal in the management of these high-risk pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…115 The earlier the diagnosis of a short cervix, the more likely the patient will deliver preterm. 1633 Compelling evidence supports the view that this condition is syndromic in nature and has multiple etiologies, 13,3437 such as a decline in progesterone action, 3848 prior cervical surgery, 4957 intra-amniotic inflammation and/ or infection, 5863 and genuine cervical insufficiency. 35,64 Patients with a mid-trimester sonographic short cervix can be offered treatment with vaginal progesterone 6573 and, for those with a history of preterm birth, a cervical cerclage 7480 may be placed.…”
Section: | Introductionmentioning
confidence: 92%
“…At present, there are some promising reports about the utility of CL measurement in other high-risk women, such as those with multiple pregnancies [22, 30], although conflicting results have been reported in symptomatic patients [26, 31, 32]. Recently, Conde-Agudelo and Romero [25] conducted a systematic review and meta-analysis and concluded that overall, the change in CL over time has a low predictive accuracy for preterm birth before 35 and 37 weeks in women with singleton gestations, irrespective of the basal risk status of the patient.…”
Section: Discussionmentioning
confidence: 99%